TINGKAT PENGETAHUAN KELUARGA TERHADAP KESEHATAN JIWA LANSIA DENGAN RIWAYAT PENYAKIT KEJIWAAN DIKABUPATEN DEMAK JAWA TENGAH - Zaky Mubarak; Siti Nafisah (NHM PRESS, 2022)
The aging process is a process that cannot be avoided. In essence, the aging process will cause changes in the elderly. An elderly person will experience changes due to decreased body function. One of these changes is a psychological change that will affect his mental health. The purpose of this study was to determine the level of family knowledge about mental health in families with a history of psychiatric disorders. The design used in this study is descriptive quantitative with a cross-sectional approach with purposive sampling technique. The number of samples is 100 respondents divided into 3 groups. The data collection procedure used was to give questionnaires to respondents, the questionnaire measurement scale using guttman and likert. The results of this study have high knowledge of 70% and low knowledge of 30%. Based on the results of the chi-square statistical test, the p value = 0.000.